Hassan Hanafi and Islamic Legal Theory: - Prihantoro, Hijrian Angga (Mazahib, 2021)
Islamic legal theory (popularly known as uá¹£Å« al-fiqh in Islamic term) runs into difficulties when dealing with social and humanities issues. Religious texts, according to Hassan Hanafiâ€™s perspective, should not only be positioned as a source of law, but also at the same time must be seen as a phenomenological experiences of religiosity. The dialectic of religious text and today's empirical context needs to be reformulated. By using phenomenological as a methodological tool, Hassan Hanafi makes an effort of reepistemification of uá¹£Å« al-fiqh reason into three typologies of consciousness; historical, eidetic, and praxis. These three aspects constitute the discursive relationship to present an anthropocentric dimension in uá¹£Å« al-fiqh reason. This article uses qualitative research methods with interpretation criticism approach. This article aims to analyze the new formula offered by Hassan Hanafiâ€™s uá¹£Å« al-fiqh reason, and to examine it to criticize the slogan â€œBack to the Qur'an and Sunnaâ€ as a phenomenon of religiosity. Keywords: Uá¹£Å« al-fiqh, Hassan Hanafi, Phenomenology, Back to the Qurâ€™an and Sunna